Fazendo desvios de circuito na revista Somtrês: O discurso das tecnologias digitais musicais antecipadas, imaginadas e abandonadas - Borges, Luis Fernando Rabello (Universidade do Vale do Rio dos Sinos, 2019)
The work presented in these pages aimed to identify traces of the music digitization frequently associated to the 21st century in Somtrês, monthly magazine of music that circulated in the pews of the country between January of 1979 and January of 1989. Somtrês was different from other similar publications of the time to dedicate more detailed way not only to the traditional agenda related to disc launches, concert coverage and interviews with artists, but also to the audio technologies of recording and reproducing audio. And within this decade of the magazine's existence, a whole set of transformations and technological innovations emerged in the field of audio and video production and reproduction, such as CD and DAT tape, VHS tape and the subsequent market video recorders and videocassettes and camcorders, and digital and polyphonic instruments for synthesizing and sampling (synthesizers and samplers) and musical note marking (MIDI controllers). The emergence and/or popularization of these and other possibilities for the digitization and storage of data capable of sound reproduction, access to video content for much more than when it was originally broadcast in the cinema or on television, and recording and creation of musical records in the increasing threat of piracy as a result of all these innovations, took place more intensely in the second half of the 1980s, which is why, in this work, mainly articles extracted from the last 40 editions of the magazine, notably from the debut, in its pages, of the Instruments section. The analysis was based on a methodological exercise of taking the discourse of the journal as an object, exercise based on the theoretical concepts of "media archeology" and "materialities of communication". Emphasizing the descriptions and photos (the “technology discourse”) of the equipment covered in Somtrês's articles, a kind of “circuitbending” was performed from the magazine's original discursive assignments. Thus, this research contemplates the magazine in its aspects less than "crisis" and more of "restlessness", that is, to emphasize the curiosity regarding the advent of certain technological innovation of production or musical reproduction, to the detriment of the brag about negative impacts on the market that such an advent could eventually cause.
Keywords: Tecnologias digitais musicais; Desvio de circuito; Revista Somtrês; Musical digital technologies; Circuitbending; Somtrês magazine; ACCNPQ::Ciências Sociais Aplicadas::Comunicação